2023
DOI: 10.1186/s12913-023-09161-9
|View full text |Cite
|
Sign up to set email alerts
|

Burnout, work engagement and work hours – how physicians’ decision to work less is associated with work-related factors

Abstract: Background According to new estimates, the health care sector will suffer a shortage of physicians in primary and specialty care. In this context, work engagement and burnout are two constructs that have gained attention recently. The aim of this study was to investigate how these constructs are related to work hour preference. Method The present study was based on the baseline survey of the long-term study of physicians with different specialties,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
1
3
0
1
Order By: Relevance
“…Data on the specific focus of the disillusion-fulfilment dimension showed that about 23% reported a state of complete disillusion, 67.5% a condition of risk of compromising their work motivations and ideals, and just under 10% a state of fulfilment. This result is also in line with previous studies that analyzed the importance of the fulfilment dimension in healthcare in the pandemic period (e.g., [50,51]). A new element revealed by this study is the assessment of the "dark side" of fulfilment, represented by disillusion in healthcare workers.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Data on the specific focus of the disillusion-fulfilment dimension showed that about 23% reported a state of complete disillusion, 67.5% a condition of risk of compromising their work motivations and ideals, and just under 10% a state of fulfilment. This result is also in line with previous studies that analyzed the importance of the fulfilment dimension in healthcare in the pandemic period (e.g., [50,51]). A new element revealed by this study is the assessment of the "dark side" of fulfilment, represented by disillusion in healthcare workers.…”
Section: Discussionsupporting
confidence: 92%
“…Concerning the COVID-19 period, Martínez-López and colleagues [50], studying healthcare workers in Spain in facilities for the elderly, highlighted the importance of fulfilment for counteracting burnout and for the sustainability of the work environment. Jung et al [51] highlighted the relationship between workload and burnout on the one hand, and work engagement and fulfilment on the other hand, in a sample of (approximately 1000) Danish healthcare workers. Lyubarova and colleagues [52], through a literature review, highlighted the gender differences present in the relationship between fulfilment and burnout, workload, and organizational task complexity.…”
Section: Fulfilment Disillusion and Burnout In Healthcarementioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al [ 16 ] reported that individuals working long hours (41–52 h/week) with diabetes had 1.85 times higher odds of CKD (95% CI 1.15–2.96, p = 0.0112) compared to those who worked ≤ 40 h/week or less. As the number of working hours increases, work-related stress can also increase [ 36 ], leading to the activation of the systemic inflammatory response, which may play a role in the A development of kidney disease [ 37 ]. Another mechanism might be dietary habit change.…”
Section: Discussionmentioning
confidence: 99%
“…Wenn Ärzt:innen am Rande der Erschöpfung arbeiten oder gar von Präsentismus die Rede ist, kann jedoch keine optimale Gesundheitsversorgung garantiert werden. Gerade neuere Studien weisen darauf hin, dass es einen Zusammenhang zwischen Arbeitszeitreduktion und hoher Arbeitsbelastung gibt [ 26 ]. Wichtig ist es daher, gemeinsam nach einer Lösung zu suchen, die die Interessen aller Beteiligten berücksichtigt.…”
Section: Diskussion Und Perspektivenunclassified